Temporal Trends in Co-trimoxazole Use Among Children on Antiretroviral Therapy and the Impact of Co-trimoxazole on Mortality Rates in Children Without Severe Immunodeficiency. (11th September 2018) - Boettiger, David C; Law, Matthew G; Sohn, Annette H; Davies, Mary-Ann; Wools-Kaloustian, Kara; Leroy, Valeriane; Yotebieng, Marcel; Vinikoor, Michael; Vreeman, Rachel; Amorissani-Folquet, Madeleine; Edmonds, Andrew; Fatti, Geoffrey; et al.
Abstract: Background: Co-trimoxazole is recommended for all children with human immunodeficiency virus. In this analysis, we evaluate trends in pediatric co-trimoxazole use and survival on co-trimoxazole in children using antiretroviral therapy (ART). Methods: We used data collected between January 1, 2006, and March 31, 2016, from the International Epidemiology Databases to Evaluate AIDS. Logistic regression was used to evaluate factors associated with using co-trimoxazole at ART initiation. Competing risk regression was used to assess factors associated with death. Results: A total of 54113 children were included in this study. The prevalence of co-trimoxazole use at ART initiation increased from 66.5% in 2006 to a peak of 85.6% in 2010 and then declined to 48.5% in 2015–2016. A similar trend was observed among children who started ART with severe immunodeficiency. After adjusting for year of ART initiation, younger age (odds ratio [OR], 1.18 for <1 vs 1 to <5 years of age [95% confidence interval (CI), 1.09–1.28]), lower height-for-age z score (OR, 1.15 for less than −3 vs greater than −2 [95% CI, 1.08–1.22]), anemia (OR, 1.08 [95% CI, 1.02–1.15]), severe immunodeficiency (OR, 1.25 [95% CI, 1.18–1.32]), and receiving care in East Africa (OR, 8.97 vs Southern Africa [95% CI, 8.17–9.85]) were associated with a high prevalence of co-trimoxazole use. Survival did not differ according to co-trimoxazole use in children without severe immunodeficiency (hazard ratio, 1.01 for nonusers versus users [95% CI, 0.77–1.34]). Conclusions: Recent declines in co-trimoxazole use may not be linked to the current shift toward early ART initiation. Randomized trial data might be needed to establish the survival benefit of co-trimoxazole in children without severe immunodeficiency. Abstract : The prevalence of co-trimoxazole use among children starting ART increased from 66.5% in 2006 to 85.6% in 2010 before declining to 48.5% in 2015–2016. The hazard of death did not differ according to co-trimoxazole use in children without severe immunodeficiency.